1992
DOI: 10.1525/ap3a.1992.3.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Powhatan's Pursestrings: On the Meaning of Surplus in a Seventeenth Century Algonkian Chiefdom

Abstract: The implicit tension in chiefly economies–between a political economy predicated on surplus supplied by a domestic economy content with sufficiency–is explored, and an example of its political and processual consequences discussed. Comparison of ethnohistoric narratives with estimation of annual agricultural production for the seventeenth century Powhatan chiefdom suggests that the expansion and increasing complexity of the Powhatan political system was not due to overpopulation but was instead a response to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…128-130;Rountree and Turner 2002, p. 32). Barker (1992) has even suggested that protohistoric depopulation triggered by Europeanintroduced epidemics was a factor in the emergence of the Powhatan political economy. Under this scenario, the curtailed tribute available from a declining population prompted military expansion by Algonquian chiefs, including Wahunsenacawh, who sought to expand their influence over greater numbers of communities.…”
Section: Early Colonial Periodmentioning
confidence: 99%
“…128-130;Rountree and Turner 2002, p. 32). Barker (1992) has even suggested that protohistoric depopulation triggered by Europeanintroduced epidemics was a factor in the emergence of the Powhatan political economy. Under this scenario, the curtailed tribute available from a declining population prompted military expansion by Algonquian chiefs, including Wahunsenacawh, who sought to expand their influence over greater numbers of communities.…”
Section: Early Colonial Periodmentioning
confidence: 99%
“…Before Jamestown, however, as punishment shifted out of the hands of local elders and communities into the hands of regional subchiefs further up the hierarchy, Wahunsonacock gained a “plurality,” not a monopoly, on the use of force (Barker :68; cf. Gleach :29–31).…”
Section: Wresting Control Of Punishment From Local Groupsmentioning
confidence: 99%
“…See alsoPotter (1993:16-17); see alsoRountree (1989:117-119) on the relationship between subchiefs and Powhatan. On tribute, in particular, seeBarker (1992).…”
mentioning
confidence: 99%
“…In fact, this system of rationing may have been one of any number of ways leader systems mediated local conflict. 36 Given the clear evidence of intergroup conflict and warfare, complex chiefdoms may have emerged in parts of the system-and this appears to have been particularly true in the South Appalachian area-as a way of combining defensive forces against common enemies, perhaps other but stronger Mississippians. 37 The social organization of the known Mississippian societies arguably made up the beginnings of a class system that would have typified a society in the early stages of developing a state mechanism.…”
Section: The Internal Organization Of the Precontact Mississippian Sy...mentioning
confidence: 99%